LOTUS-domain proteins: developmental effectors from a molecular perspective - Kubíková, Jana; Reinig, Rebecca; Salgania, Harpreet Kaur; Jeske, Mandy (Biological chemistry, 2020)
Abstract The LOTUS domain (also known as OST-HTH) is a highly conserved protein domain found in a variety of bacteria and eukaryotes. In animals, the LOTUS domain is present in the proteins Oskar, TDRD5/Tejas, TDRD7/TRAP/Tapas, and MARF1/Limkain B1, all of which play essential roles in animal development, in particular during oogenesis and/or spermatogenesis. This review summarizes the diverse biological as well as molecular functions of LOTUS-domain proteins and discusses their roles as helicase effectors, post-transcriptional regulators, and critical cofactors of piRNA-mediated transcript silencing.
Gesehen am 25.01.2021